Lingkar Kepala dengan Masa Perkembangan pada Bayi usia 0 -12 Bulan - I Nyoman Ribek; I Ketut Labir (Jurusan Keperawatan Poltekkes Kemenkes Denpasar, 2013)
This study aimed to determine the relationship of children head circumference towards theirgrowth in infants aged 0-12 months. This study uses description method with correlative studydesign. Sample consists of 30 people who were selected by stratified random sampling. Datawas collected through observation, measurement of head circumference and examination usingDDST form. As the results, 90% had normal head circumference meanwhile the other 10%hadmicrosefaly. In its development, 87% were classifiednormal and 13% were classified assuspected. Based on the result using the Spearman Rank Test,there is a significant correlationbetween the baby's head circumference towards their growth with significance level of p = 0.05.